Frankophila dalevittii, a new freshwater diatom (Bacillariophyta) from Campbell Island - van De Vijver, Bart; Ballings, Petra; Goeyers, Charlotte (Phytotaxa, 2020)
During a survey of the freshwater diatom flora of the sub-Antarctic Campbell Island, located in the southern Pacific Ocean, an unknown freshwater diatom was observed forming long colonies using linking spines. Detailed morphological analysis based on light and scanning electron microscopical observations and comparison with all known Frankophila taxa worldwide justified the description of this unknown taxon as a new species within the genus Frankophila: Frankophila dalevittii Van de Vijver & Goeyers sp. nov. The new taxon is characterized by the presence of well-developed linking spines, the absence of external raphe slits and the presence of internal raphe slits, biseriate striae composed of relatively large areolae and a large axial area. Despite the absence of the external raphe slits, the species is best placed within the genus Frankophila. The new species is described and illustrated and compared with all other Frankophila taxa.